Análisis financiero con la aplicación de la metodología CAMELS para determinar los riesgos financieros en las cooperativas de ahorro y crédito del segmento 1 zonal 3, periodo 2019-2021. - Chuga Lara, Melisa Katherine (2024)
ABSTRACT: Savings and credit cooperatives are agents of economic dynamism and an essential part of Ecuador's economic development. They contribute to financial inclusion, agricultural development, the promotion of entrepreneurship and economic stability, and improving the quality of life of their members and the regional economy in general. “Currently, there is quality information on the 400 Savings and Credit Cooperatives (COACS) that are active, making up this important sector of the national financial system” (Superintendency of Popular and Solidarity Economy [SEPS], 2024). Because of its importance, the objective of this research was to carry out a financial analysis using the CAMELS methodology to determine the financial risks in the savings and credit cooperatives of segment 1 zone 3 during the period 2019-2021. The research methodology applied was deductive with a quantitative approach based on a non-experimental design of an exploratory and documentary type. We worked with a population of 12 savings and credit cooperatives from segment 1, zone 3. Through documentary analysis and indirect observation techniques, information was collected from the consolidated financial statements corresponding to the periods 2019, 2020 and 2021 from the portal of the Superintendency of Popular and Solidarity Economy (DataSeps) for the application of the CAMELS methodology. As a result, it was proved that the CAMELS methodology was effective in the evaluation of financial risks in the evaluated cooperatives, classifying them into two main groups: High Performance and Moderate Performance, among the cooperatives that demonstrated solid financial management and an excellent capacity to manage risks is the COAC of the Small Business of Cotopaxi Limitada, among the cooperatives that show areas that require attention to improve their financial stability is the COAC Kullki Wasi Ltda. In summary, results revealed considerable variability in asset quality and operational management effectiveness among cooperatives. Additionally, significant challenges were identified in terms of profitability and liquidity, highlighting the need for robust financial management. The application of this methodology not only provided a detailed diagnosis of the financial situation, but also proved to be an effective tool for the identification and management of financial risks in the cooperative sector. Keywords: Financial Analysis, Methodology, CAMELS, Savings and credit cooperatives, Risks.